Probing the 3D Structure and Function of a Cation/H+ Exchanger in Plant Reproduction - Czerny, Daniel (My University, 2015)
Maintaining intracellular pH and K+ homeostasis are necessary for a cell to divide, grow, and communicate with other cell types. How a cell responds to stimuli and subsequently regulates intracellular pH and K+ content are largely unknown. Ion transporters, including cation/H+ exchangers are one potential determinant of intracellular pH and K+ content. A novel family of CHX transporters, predicted to exchange a cation for a H+, is found in all land plants, though their functions in the plant and the mode of transport are mostly unknown. What is the mode of transport of Arabidopsis thaliana CHX17? Model structures of the CHX17 transmembrane domain were built from two crystallized bacterial Na+/H+ antiporters. Based on protein architecture and homology, residues were selected for mutagenesis and CHX17 activity was tested in yeast. Thr170 and Lys383 in the discontinuous α-helices of transmembrane 4 and 11, and Asp201 and Lys355 in the middle of transmembranes 5 and 10 are necessary for CHX17 activity. Results suggest these are core residues that participate in cation binding and/or catalysis. Glu111 near the cytosolic surface of CHX17 was necessary for activity, suggesting CHX17 could be regulated by cytosolic pH. Thus the protein fold and mode of transport of Arabidopsis CHX17 resemble a K+/H+ exchanger. What roles do K+/H+ exchangers play in plant reproduction? chx17/18/19 mutant plants showed a 56%-77% reduction in seed set though the biological basis was unknown. Reciprocal crosses showed reduced seed set was primarily caused by defects in the male gametophyte. Mutant chx17/18/19 pollen grains developed normally and pollen tubes grew and reached most ovules. However, half the ovules receiving a mutant pollen tube failed to develop. Wild-type pistils that received chx17/18/19 pollen showed unfertilized ovules, ovules with single fertilizations, and some embryos that developed similarly to wild-type. Thus, some triple mutant pollen showed failure to complete fertilization. When fertilization was successful, embryos from self-fertilized chx17/18/19 pods showed delays in development. Our findings suggest maintenance of pH and K+ homeostasis in endomembrane compartments by CHX17 and its homologs could regulate membrane trafficking events necessary for pollen tube growth, male gamete fusion, and embryo development.
Keywords: Cellular biology; Botany; Genetics; antiport; Arabidopsis thaliana; cation; pH; pollen; reproduction